2018
DOI: 10.1177/1533317517753362
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of the GO Game Intervention on Cognitive Function

Abstract: This study investigated the effects of an intervention using the game "GO" on cognitive function in nursing home residents and evaluated the acquisition of GO according to each stage of dementia. Participants were randomly assigned to either the GO intervention group or a control group, and the intervention was performed once weekly for 15 weeks. Cognitive tests were conducted before and after intervention, and 17 participants were included in the final analysis. Analysis of covariance demonstrated that in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…The details of the nine studies targeted to people with cognitive decline are described in Table and Supporting Table 2. Regarding the research design, five of the nine were RCT, three were cluster RCT and the other did not include a control group (pretest–post‐test design) . The characteristics of the participants were as follows: (i) the mean age of the participants was ≥85 years in three and 75–84 years in six, with no studies identified for participants aged 60–74 years, a population that is commonly found in studies for healthy older adults; and (ii) the ratio of women was ≥50% in all studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the nine studies targeted to people with cognitive decline are described in Table and Supporting Table 2. Regarding the research design, five of the nine were RCT, three were cluster RCT and the other did not include a control group (pretest–post‐test design) . The characteristics of the participants were as follows: (i) the mean age of the participants was ≥85 years in three and 75–84 years in six, with no studies identified for participants aged 60–74 years, a population that is commonly found in studies for healthy older adults; and (ii) the ratio of women was ≥50% in all studies …”
Section: Resultsmentioning
confidence: 99%
“…Art and board games ( n = 3 each) were the most common intervention tools in studies targeting people with cognitive decline. Only one study each used handicrafts, writing, reading and cooking ( n = 1 each).…”
Section: Resultsmentioning
confidence: 99%
“…Telepresence robots, for example, are remotely controlled mobile video-conference systems that can improve social participation through videoconferencing with family and friends anywhere in the world. Other robotic systems can provide stimulating entertainment, and virtual reality can stimulate new experiences and reduce apathy 27,28 . Other robots include cute and cuddly therapeutic pet-type robots, such as Paro, which was developed in Japan and modelled on a baby harp seal 29 .…”
Section: [H2] Therapeutic Technologiesmentioning
confidence: 99%
“…Based on our pilot study, 14 we hypothesized a medium effect size of the change of scores in the DSTs and VMSTs, which are the main outcomes in this study, among the three groups. The sample size was calculated with G*power (http://www.gpower.hhu.de) based on 95% power, a two-sided hypothesis test, an alpha level of 5%, and an analysis of variance model between groups over time.…”
Section: Sample Sizementioning
confidence: 99%
“…We previously investigated the effects of Go on cognitive function in patients with dementia and in persons with mild cognitive impairment (MCI) who were living in a nursing home. 14 The results indicated that Go might improve working memory. However, confounding factors such as social interaction with others were inevitable.…”
Section: Introductionmentioning
confidence: 96%